A Bibliometrics Analysis on Teacher’s Feedback Research Based on CiteSpace through Data Visualization - Xie, Wanji (Scientific programming, 2022)
Teacher feedback has played a pivotal role in students’ foreign language learning. This article aims to gain a more comprehensive insight into the current situation and development trend of teacher feedback in core leading Chinese Academic Journal within the last decade using both CiteSpace and narrative analysis. Results show that (1) research on teacher feedback has undergone a dynamic increase in the past 10 years, with 2013 the summit; (2) research subjects have become more diversified rather than focusing only on undergraduates learning English; written and oral feedback are still two major research classifications; (3) empirical studies still dominates the field while theory exploration still employs nonempirical research. Future research should emphasize more on sustained development of authors and explore this field using more cross-discipline theories and taking multiple theoretical perspectives.